Dynamics of Extreme Violence during the Indonesian National Revolution in Subang, 1945-1949 - Aji Samsudin; Ibnu Sodiq (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This research aims to reconstruct the patterns and impacts of violence that occurred in the Subang region, particularly in the Pamanoekan and Tjiasem lands (P & T Lands), during the early period of the Indonesian War of Independence. Subang was a strategic area with vital economic infrastructure, making it a focal point of conflict between Dutch military interests and the guerrilla tactics of Indonesian fighters. Using the critical historical method, this study examines primary sources, including newspaper reports, memoirs, and letters from Dutch officers. The findings show that violence in Subang occurred in two main forms: infrastructure sabotage by Indonesian fighters and "cleansing" operations (zuivering) conducted by the Dutch army. Dutch military operations often used euphemisms to cover up repressive acts, such as the burning of villages (scorched earth) and mass executions of citizens suspected of being "troublemakers". In addition, this study highlights the precarious situation of civilians living in an acute climate of suspicion, in which they became victims of both parties to the conflict. The results conclude that violence in Subang was not merely an excess of war, but part of a systematic military strategy to control territory and logistics, which resulted in widespread suffering for the civilian population.